FENOMENA UMKM BERBAGI “JUMAT BERKAH” DI YOGYAKARTA - Ari Dyah Sinta; Shulhan; Lessy, Zulkipli (IAIN PONOROGO, 2024)
Nowadays, philanthropy is present in every aspect of society. The absence of the state or the empty role of the state in society has led to an attitude of self-protection that gives rise to all practices of assurance through assistance. The existence of a religious narrative within oneself and the desire to prosper in the community are the main reasons why they want to help. Then, the assistance is institutionalized; there is distrust in managing the assistance, so some givers directly assist, such as what is done by MSME owners who carry out the